Investigation of Mechanical Properties and Microstructure of AZ31-SiC-Graphite Hybrid Nanocomposites Fabricated by Bottom Pouring-Type Stir Casting Machines - Itha Veeranjaneyulu; Vemulapalli Chittaranjan Das; Srikanth Karumuri (Advances in Materials Science and Engineering)
In this study, a bottom pouring-type stir casting machine was used to create AZ31 magnesium alloy hybrid nanocomposites with varying weight percentages (0, 3, 5, and 7) of silicon carbide (SiC) and graphite (Gr) particles. Investigations have been made into the mechanical characteristics and microstructural distribution of manufactured hybrid nanocomposites. The outcomes demonstrate that the mechanical characteristics and uniform distribution of SiC and Gr particles are enhanced compared to those of the base alloy. In comparison to monolithic AZ31 alloy, microhardness, ultimate tensile strength (UTS), yield strength (YS), and compressive strength (CS) were raised by about 54%, 68%, 82%, and 107%, respectively. The presence of reinforced particles, the uniform distribution of particles, and the strong interfacial connection between the matrix and reinforcement all contribute to the improvement of mechanical properties. However, the addition of 7 wt. % SiC/Gr showed good mechanical properties compared to the base alloy. The microstructure of nanocomposites was analyzed using a scanning electron microscope (SEM), and particles were described using energy-dispersive spectroscopy (EDS).